Expression of inhibitory receptors by B cells in chronic human infectious diseases restricts responses to membrane-associated antigens - Ambegaonkar, Abhijit A. (Sci Adv, 2020)
Chronic human infectious diseases, including malaria, are associated with a large expansion of a phenotypically and transcriptionally distinct subpopulation of B cells distinguished by their high expression of a variety of inhibitory receptors including FcγRIIB. Because these B cells, termed atypical memory B cells (MBCs), are unable to respond to soluble antigens, it was suggested that they contributed to the poor acquisition of immunity in chronic infections. Here, we show that the high expression of FcγRIIB restricts atypical MBC responses to membrane-associated antigens that function to actively exclude FcγRIIB from the B cell immune synapse and include the co-receptor CD19, allowing B cell antigen receptor signaling and differentiation toward plasma cells. Thus, chronic infectious diseases result in the expansion of B cells that robustly respond to antigens that associate with cell surfaces, such as antigens in immune complexes, but are unable to respond to fully soluble antigens, such as self-antigens.